Последний самурай: [роман] / Хелен Девитт - Девитт Хелен (Лайвбук, 2021)
Экземпляры: Камская библиотека (20220622) / Инвентарный номер: 15461 / Цена: / Сис.шифр: 84(7Coe)-44 / Авт.знак: Д 25 / ББК: 84(7Coe)-44